Cerebral palsy and socioeconomic status: a retrospective cohort study. Issue 1 (21st December 2004) - Sundrum, R; Logan, S; Wallace, A; Spencer, N
Abstract : Aims: To study the relation between risk of cerebral palsy and socioeconomic status. Methods: A total of 293 children with a diagnosis of cerebral palsy out of 105 760 live births between 1 January 1982 and 31 December 1997 were identified from the special conditions sub-file of the West Sussex Computerised Child Health System. Results: There was a linear association between risk of cerebral palsy and socioeconomic status (SES) measured by the Registrar General's social class (RGSC) and enumeration district (ED) ranked into quintiles by the Townsend Deprivation Index derived from 1991 census data. Fifty one per cent and 30% of cases of cerebral palsy were statistically "attributable" to inequality in SES using the RGSC and ED quintile respectively. A linear association was also noted for singleton live births. The association between risk of cerebral palsy and ED quintile persisted in a logistic regression model that included birth weight and gestational age, although that between RGSC and cerebral palsy no longer reached conventional levels of statistical significance after adjustment. Conclusions: A strong association was observed between socioeconomic status and the risk of cerebral palsy, which was only partly accounted for by the known social gradients in birth weight and gestational age.